Indian Sensibility through English Language: A Critical Analysis of Keats was a Tuber by Poile Sengupta - Rao, Monika (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The study of English language in this age of globalization is essential because English has become global language today. Therefore, to learn and to write in English is an utter need of present time. It is also pertinent to see that all original knowledge of every subject like- Science, Social Sciences- as Political Science, Economics and Arts lies in English language only. If one wants to learn the above subjects he must learn English language. Lord Macaulay in his ‘Minute on Indian Education’ stated that, “ We must at present do our best to form a class, who may be interpreters between us and the millions of whom we govern- a class of persons Indian in blood and color, but English in tastes, in opinions, in morals and in intellect…” It is well known fact that British ruled upon this country for more than two hundred years and India got freedom from British in 1947, but they put back their English language for Indians. It is the most important language of communication between different countries. In India, people of different states have their own languages but English language has been brought to us as a connecting link among various states of India. Today, English is essential in educational institutions, trading centers, corporate sectors etc. It has taken over all the regional and vernacular language too. In this paper, the play which I intend to talk about is Keats was a Tuber by Poile Sengupta. The play is a satire on Indian English Language; It questions the importance and ownership of the English language by Indians.